1996
DOI: 10.1002/(sici)1097-0142(19961215)78:12<2510::aid-cncr10>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary acute promyelocytic leukemia

Abstract: BACKGROUND. Extramedullary acute promyelocytic leukemia (APL) is rare, and said to be more common after treatment with all-trans retinoic acid (ATRA) than after any other treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 25 publications
0
49
0
2
Order By: Relevance
“…31 None of the three AML-M3 patients in our study had exposure to ATRA prior to SCT, although one (UPN 537), as we previously reported, 32 had received extensive isotretinoin (13-cis retinoic acid) maintenance therapy before transplant. Notably, of the three AML-M3 EM relapse patients, one was of East Indian, one was of Asian, and one was of Northern European descent.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…31 None of the three AML-M3 patients in our study had exposure to ATRA prior to SCT, although one (UPN 537), as we previously reported, 32 had received extensive isotretinoin (13-cis retinoic acid) maintenance therapy before transplant. Notably, of the three AML-M3 EM relapse patients, one was of East Indian, one was of Asian, and one was of Northern European descent.…”
Section: Discussionmentioning
confidence: 69%
“…30 It is of particular interest that three patients with isolated post-SCT EM relapse had AML-M3, a disease that has rarely been reported to involve EM sites. 28,31 However, of the five published cases of isolated AML EM relapse following BuCy, including an earlier report from our centre, 13,32 three of the patients had AML-M3. It could be argued that the additional cytogenetic abnormalities in two of our three AML-M3 patients (tetrasomy 8 and three extra copies of chromosome 21, respectively), signified a more aggressive form of AML-M3 with a propensity for EM disease.…”
Section: Discussionmentioning
confidence: 84%
“…Less than 30 cases have been reported in the literature until now and the diagnosis in most of these cases was not confirmed by cytogenetic or molecular studies. 6,7,9 However, since the first report by Weiss and Warrell, 5 extramedullary relapses in APL patients receiving ATRA induction have been detected more frequently than before, 6,7,10 but the correlation between ATRA usage and the subsequent extramedullary disease remains obscure. In this retrospective study, it was demonstrated that patients receiving ATRA induction had an increased risk in extramedullary relapse compared with those with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…This event was rarely reported in those patients with cytogenectically and/or molecularly con- firmed APL who were treated with chemotherapy alone. [5][6][7] However, it is not yet clear whether ATRA truly increases the risk of extramedullary relapse and what are the risk factors. In this study, relapsed APL patients treated with or without ATRA were compared for the incidence of extramedullary involvement.…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been suggested that cutaneous cases of extramedullary disease in acute promyelocytic leukemia may have a characteristic predilection to occur at sites of puncture for blood and bone marrow samples and that treatment with ATRA may predispose these patients to extramedullary relapse. 7,8 We believe that fluorescence in situ hybridization (FISH) provides an efficient and reliable method of detecting the t(15;17) rearrangement associated with acute promyelocytic leukemia in suspected cases of leukemia cutis, and will aid in distinguishing cutaneous involvement by acute promyelocytic leukemia from reactive processes or other neoplastic processes that can occur in this setting.…”
mentioning
confidence: 99%